Clinical Features and Treatment Results of Children with Diffuse Large B-Cell Lymphoma. (1st September 2014) - Ataş, Erman; Kutluk, M. Tezer; Akyüz, Canan; Kale, Gülsev; Varan, Ali; Yalçın, Bilgehan; Aydın, Burça; Büyükpamukçu, Münevver
<x xml:space="preserve">Abstract</x> The demographic, clinical characteristics, and treatment groups of 33 children with diffuse large B-cell lymphoma (DLBCL) were recorded and analyzed among 1486 non-Hodgkin lymphoma (NHL) cases since 1972. The median age was 9.7 years (range 1.4–16.9) and male/female ratio was 24/9 = 2.6. Kaplan–Meier methods and logrank tests were used in treatment analysis. The frequency of DLBCL among 1486 NHL cases was 2.2%, however, the percentage was 9.3% in cases diagnosed after 2000. The event-free survival (EFS) and overall survival (OS) rates for 33 children were 61% and 65.1% at 5 years, respectively. The EFS and OS rates of low stage (stages I and II) disease decreased to lower level in advanced stage (stages III and IV) disease. Associated conditions and ages older than 14 years were found as poor prognostic factors in multivariate analysis. The survival rates in children with DLBCL need further improvement. This is mainly related with late referral of those children with advanced disease. The proper diagnosis and early referral is essential in these children for a better survival rate. The children with associated conditions and older children must be handled with care since these are found as poor prognostic factors.